Comparison of Methods for the Analysis of the Parallel Resonant Converter with Capacitive Output Filter - Dürbaum, Thomas; et al. (12th European Conference on Power Electronics and Applications - EPE 2007, 2 - 5 September 2007, Aalborg, Denmark, 2007)
Several different approaches for the investigation of the steady-state properties of resonant converters have been published to date. In addition to solving the occurring equations in the time domain, which turns out to be quite cumbersome, the designer can make use of approximate approaches in the frequency domain. Two of these methods are compared to the exact solution with regard to their accuracy and mathematical complexity within this paper for the parallel loaded resonant LC converter with capacitive output filter. Some practical aspects are discussed by means of measured voltage conversion ratios.
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.lselek.compar
Keywords: Resonant converter; Soft switching; ZVS converters